SOCIAL LIFE CYCLE ASSESSMENT OF ARABICA COFFEE PRODUCTION BASED ON ITS MANAGEMENT SYSTEM IN SAMOSIR REGENCY, NORTH SUMATRA PROVINCE, INDONESIA - Hendris Syah Putra; Herlyna Novasari Siahaan (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
The growing global demand for coffee has heightened concerns about its social sustainability, particularly in smallholder-based production systems where empirical evidence remains limited. This study assesses the social impacts of Arabica coffee production in Samosir Regency, North Sumatra, Indonesia, using the Social Life Cycle Assessment (S-LCA) framework and the 2020 United Nations Environment Programme (UNEP) reference-scale approach. Six micro-scale Arabica coffee enterprises representing three management systems—private enterprises, middlemen, and a farmer group—were evaluated across six stakeholder categories and 26 social subcategories. All management systems achieved a “highly sustainable” rating, with social sustainability index scores of 0.88 for private enterprises, 0.87 for the farmer group, and 0.86 for middlemen. Key social hotspots were identified in occupational health and safety, the absence of written employment contracts, and limited employer-provided social security coverage. The findings indicate that targeted, low-cost interventions—such as basic OHS provision, simple employment contract templates, and facilitated enrolment in social security schemes—could significantly strengthen social outcomes without imposing excessive financial burdens on micro-enterprises, thereby enhancing social equity and resilience within Indonesia’s Arabica coffee value chain.